PERBANDINGAN QUALITY OF SERVICE JARINGAN MENGGUNAKAN ANTENA WAJAN BOLIC DAN ANTENA WIFI GUN - Tomi Hidayat; Ilham Faisal; Mufida Khairani (Universitas Harapan Medan, 2020)
MiFi (Mini Wifi) is an internet service provider tool that can share internet connections with devices that are connected to it, unfortunately MiFi (Mini Wifi) has a very small hotspot range, so users are required to be close to MiFi (Mini Wifi) so that to connect, the farther a device is from MiFi (Mini Wifi), the less internet speed is given to the device. From this problem, researchers intend to expand the range of reception of hotspot signals on the MiFi (Mini Wifi), namely by using a pan grid antenna and a wifi gun antenna. Therefore, this study aims to compare the level of difference in the quality of network traffic using a griddle antenna and a wifi gun antenna in providing Quality of Service (QoS) services when capturing long-distance signals. The result of this comparison is as a reference for the community to choose the best long distance signal catcher between the griddle antenna and the wifi gun antenna.